Isobaric vapor-liquid equilibrium data for binary systems of anisole with methyl acetate, ethyl acetate, n-propyl acetate, and isopropyl acetate at 93.9 kPa - Bhoi, Bharat R.; Mali, Nilesh A.; Joshi, Sunil S. (Journal of Chemical and Engineering Data, 2018)
The present work reports experimental isobaric vapor-liquid equilibrium data at 93.9 kPa pressure using a dynamic recirculation still for four binary pairs of acetates with anisole. The suitability of the experimental data for modeling was established by performing the Herington area test, Van Ness test, and mean absolute deviation test. Binary interaction parameters necessary for process modeling were derived through the regression of the VLE data for Wilson, NRTL, and UNIQUAC activity coefficient models with a suitable objective function. VLE data in the form of T-x, y plots indicates no formation of azeotropes for all pairs.